2005
DOI: 10.1902/jop.2005.76.12.2276
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles in Peripheral Blood and Whole Blood Cell Cultures Associated With Aggressive Periodontitis, Juvenile Idiopathic Arthritis, and Rheumatoid Arthritis

Abstract: Patients with aggressive periodontitis and types of arthritis presented with similar components of blood cytokine profiles distinguishing them from individuals free of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
2
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 67 publications
6
82
2
7
Order By: Relevance
“…c) Rheumatoid arthritis (RA): Recent studies seem to assert the existence of a relationship between periodontal disease and RA (19)(20)(21)(22)(23)(24)(25)(26)(27). Some authors even affirm that the two diseases have so much in common that they represent the same disease (28).…”
Section: Oral Capillaroscopy and Autoimmune Pathologiesmentioning
confidence: 99%
“…c) Rheumatoid arthritis (RA): Recent studies seem to assert the existence of a relationship between periodontal disease and RA (19)(20)(21)(22)(23)(24)(25)(26)(27). Some authors even affirm that the two diseases have so much in common that they represent the same disease (28).…”
Section: Oral Capillaroscopy and Autoimmune Pathologiesmentioning
confidence: 99%
“…This increase in pro-inflammatory TNF-α during periodontitis has been well documented [35], and it is known to play a substantial role in periodontitis mediated bone loss [36]. The concomitant increase in anti-inflammatory IL-10 in the periodontitis group is however more surprising, although it has been previously observed [37][38][39]. One hypothesis explaining the observed concomitant pro-and anti-inflammatory response is that aggressive periodontitis would stimulate a strong increase in TNF-α, which in turn could activate a counteracting anti-inflammatory IL-10 response to avoid overactivation of inflammation.…”
mentioning
confidence: 84%
“…Another hypothesis would be that during chronic generalised periodontitis, IL-10 would increase resulting in an "anti-inflammatory" state in the mouth, facilitating the dissemination of dental bacteria to extra-oral sites, which then would activate a proinflammatory response in the foetal-placental unit and therefore trigger PTB. For example, Havemose et al showed a concomitant increase in TNF-α and IL-10 in patients with generalised aggressive periodontitis, but IL-10 alone was not increased in patients with localised aggressive periodontitis [38].…”
Section: Page 6 Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 is a multifunction cytokine that has a wide range of biological activities and shows markedly elevated levels in oJIA patients [20].…”
Section: Introductionmentioning
confidence: 99%